Prevalence of Sleep Disturbances and Sleep Quality in Chinese Healthcare Workers During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Xia, Lei; Chen, Changhao; Liu, Zhiqiang; Luo, Xiangfen; Guo, Chunyan; Liu, Zhiwei; Zhang, Kai; Liu, Huanzhong (Frontiers in Psychiatry, 2021)
Objectives: Healthcare workers (HWs) experienced high levels of work stress during the COVID-19 pandemic, leading to a high risk of sleep disturbances. This meta-analysis aimed to explore the prevalence of sleep disturbances and sleep quality in Chinese HWs during the COVID-19 pandemic. Methods: English (PubMed, Embase, PsycINFO, Web of Science, and Cochrane) and Chinese databases (WanFang, Chinese National Knowledge Infrastructure, and SinoMed) were systematically and independently searched for relevant studies published from December 1, 2019 to May 20, 2020. Results: The pooled prevalence of sleep disturbances and sleep quality were calculated using random-effects model. A total of 18 studies involving 12,736 Chinese HWs were included in the meta-analysis. The pooled prevalence of sleep disturbances in Chinese HWs was 45.1% (95%CI: 37.2%-53.1%). We found that the prevalence of sleep disturbances varied between frontline, infected, and non-frontline HWs (Q = 96.96, p < 0.001), females and males (Q = 9.10, p = 0.003), and studies using different assessment instruments (Q = 96.05, p < 0.001). In addition, the pooled mean total score of Pittsburgh Sleep Quality Assessment (PSQI) was 9.83 (95%CI: 8.61-11.04), and the score of Insomnia Severity Index (ISI) was 4.80 (95%CI: 1.07-8.52). HWs from Wuhan had a higher total score of PSQI than those from other regions (Q = 9.21, p = 0.002). Conclusion: Sleep disturbances were common in Chinese HWs during the COVID-19 pandemic, particularly in the frontline and infected HWs. Our results indicate the heavy mental health burden of HWs during the COVID-19 pandemic in China, and provide other countries with valuable information that may apply to each other in the crisis.